A new invasive Ptinella Motschulsky from Europe and North America (Coleoptera: Ptiliidae) - Vorst, Oscar (Zootaxa, 2012)
Ptinella populicola sp. n. is described from material recently collected in the Netherlands. The habitus, spermatheca and aede-agus are illustrated. The only earlier specimens known are from Maryland (USA). The species is considered introduced into Europe, possibly being of Nearctic origin.